2016
DOI: 10.1002/2016ja023100
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the geoeffectiveness of shocks and sheaths at 1 AU

Abstract: We identify all fast‐mode forward shocks, whose sheath regions resulted in a moderate (56 cases) or intense (38 cases) geomagnetic storm during 18.5 years from January 1997 to June 2015. We study their main properties, interplanetary causes, and geoeffects. We find that half (49/94) such shocks are associated with interacting coronal mass ejections (CMEs), as they are either shocks propagating into a preceding CME (35 cases) or a shock propagating into the sheath region of a preceding shock (14 cases). About h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 90 publications
(184 reference statements)
3
69
1
Order By: Relevance
“…The shock/compression time usually indicates the beginning of the storm initial phase, when S Y M ‐ H goes up, whereas the IMF B z rotating southward time indicates the beginning of the storm main phase, when S Y M ‐ H starts to decrease. The amount of energy deposited in the upper atmosphere high‐latitude regions by the latter is typically larger than the amount of energy deposited by the former due to its higher geoeffectiveness (Lugaz et al, ; Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The shock/compression time usually indicates the beginning of the storm initial phase, when S Y M ‐ H goes up, whereas the IMF B z rotating southward time indicates the beginning of the storm main phase, when S Y M ‐ H starts to decrease. The amount of energy deposited in the upper atmosphere high‐latitude regions by the latter is typically larger than the amount of energy deposited by the former due to its higher geoeffectiveness (Lugaz et al, ; Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, Lugaz et al . [] found that geoeffective shock sheaths may consist of two populations: (1) those associated with shocks within transients, that is ICME‐ICME or ICME‐corotating interaction region interactions, and (2) shock sheaths associated with isolated ICMEs that we have investigated in the study. They found the former populations to be more effective storm producers.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, preferential occurrence of interplanetary shocks was found in July and November (Echer et al, ). So we examine solar wind and geomagnetic conditions during the great‐FEE days using the following parameters: the solar wind speed V as the best predictor of substorm probability (e.g., Newell et al, ) and as a factor influencing interplanetary shock parameters (e.g., Lugaz et al, ); a parameter of interplanetary electric field fluctuations VδB calculated by an expression VδB = VδitalicBz2+δitalicBy2, where ()δitalicBz2 and ()δitalicBy2 are variances of the IMF B z and B y components; and AL index of substorm activity.…”
Section: Discussionmentioning
confidence: 99%